Continuing professional development lifelong learning of millions - Friedman, Andrew L. (Routledge, 2012)
Continuing Professional Development (CPD) is the means by which the professions across the world ensure that their knowledge and skills remain up to date and relevant to changing needs and environments. CPD significantly contributes to the quality and reputation of the professions and therefore to the quality of national and international social life and economic well being.